Physiotherapy Management in Fifth Week Post Operation of Ankle Fractur Weber C in Wonosari General Hospital: A Case Study - Fitria, Ida; Widodo, Agus; Ismadi, I (Academic Physiotherapy Conference Proceeding, 2022)
Introduction: According to the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD), there were 178 million cases of fractures in 2019, a 33.4% increase from 1990. There were 76.4 million cases of fractures in women and 120 million in men. One of the top three anatomical sites for fracture in terms of prevalence is the ankle. The Weber C ankle fracture is a fracture that occur above syndesmosis-level and pronation-external ankle rotation is the most common trauma mechanism. The focus of intervention in the first to fifth week after surgery are minimizing the pain, reduce edema, and increase ankle joint range of motion.Case Presentation: Mr. B, 23, was taken to Wonosari General Hospital's emergency room following a hard impact on his right leg while playing soccer on Sunday, March 13 in the afternoon. An x-ray examination revealed a complete fractured 1/3 of the distal fibula dextra with a Weber C type of fracture. On Monday March 14, the patient underwent surgery using the ORIF approach without syndesmosis stabilization. Mr. B were advised to see an orthopaedic once a week and were taken to physiotherapy in week five. Following the operation, the patient did exercises to strengthen the thigh muscles as well as the upper body, but no ankle exercises were performed.Management and outcome: Mr. B received a total of six physiotherapy interventions. The physiotherapy interventions given include: ankle elevation, IASTM, active ROM exercise, hold relax stretching, and strengthening. After undergoing the intervention six times, there was a reduction in pain during dorsi flexion and inversion, as well as a reduction in edema, increase of ankle joint range of motion, an improvement in muscle strength, and an improvement of functional ability (AOFAS).Discussion: The patient went to physiotherapy at week 5 postoperatively with the condition still wearing the bandage, visible signs of inflammation, and using crutches with non weight-bearing. The intervention administered in week 5 and 6 are aimed at reducing pain, reducing edema, and increasing ankle joint range of motion. At week 6-7 the intervention is added with strengthening and weight bearing exercises.Conclussion: There was a decrease in pain, edema, an increase in range of motion, an improvement in muscle strength, and an increase in functional capacity after receiving the physiotherapy intervention for six times. A significant improvement is a decrease in pain during dorsi flexion and an increase in muscle strength in plantar flexion.